The Eloquence of Silence in Taha Hussein’s Al-Ayyam (The Days) - Rooh allah Nasiri (دراسات فی اللغه العربیه و آدابها, 2018)
Communicative silence may reveal people’s inner meanings and transfer specific emotions or thoughts to the audience. However, the degree of the eloquence of silence depends on the power of eloquence which silence has chosen to bestow, its audience, and the sentences used before and after it. Therefore, it seems silence and its meanings are issues worth investigating. Taha Hussein has written his autobiography in a book entitled Al-Ayyam or the Days. His blindness has had a considerable effect on his introspection and silence. Silence can be observed with different meanings everywhere in this book. By thinking about the meanings of Taha Hussein’s silence, one can understand dimensions of his personality, emotions, and thoughts. In the present study, which uses a descriptive-analytical method, the application of silence in events occurring in Al-Ayyam (the Days) is investigated in order that its role in communicating meaning is revealed, as silence sometimes indicates issues which verbal signs are unable to convey. The results of the study indicate that Taha Hussein’s silence is not of secondary importance, after the verbal signs, in conveying meaning; in fact, it has the main role in transferring explicit and implicit meanings. In addition, his silence indicates his self-respect and self-esteem. Taha Hussein sometimes, using body language, expresses intended meanings and sometimes in silence, hides his pain. Sometimes, one way to know people is their silence because both language and silence are rooted in human intentionality.